THE LIFE OF THE NIQAB AND SIRWAL; Phenomenological Study of Family Power Relations to Stigma - Mohammad Maulana Iqbal (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
This research departs from the widespread stigmatization experienced by those who wear the niqab and sirwal. Society views this attribute negatively because one of them is the actions of terrorists, suicide bombers and others, who carry out their actions using a niqab or sirwal. So this study aims to explore the experiences of the niqab and sirwal users in the private sphere, such as the family and the public sphere in society. To see these two contexts, this study uses the perspective of power relations theory from Michel Foucault and the Stigma concept from Erving Goffman. Meanwhile, methodologically, this study uses a qualitative approach to explore the experiences of the niqab and sirwal users. The findings in this study are that women who wear the niqab in power relations with their parents experience discrimination and social control regarding their attributes. In contrast to sirwal users, who are more liberated by their families in using attributes. Meanwhile, in the public sphere, niqab women again experienced verbal harassment from the public, unlike sirwal, who never experienced harassment. In this case, a woman wearing a niqab is verbally abused not only because she wears a niqab but because she is a woman who is considered inferior in a patriarchal society. In addition, in this case, niqab women experience double discrimination in private and public spaces.